(untitled) (International Journal of Food and Nutritional Sciences, 2022)
In the present study the basic set B3LYP/ LanL2Dz level used and investigated 3d transition metal monoborides utilizing the density functional approach. The dimers, the lowest spin state, bond length, vibrational frequencies are calculated. These dimers’ cation and anion are also investigated